1989
DOI: 10.1207/s15327051hci0403_3
|View full text |Cite
|
Sign up to set email alerts
|

Finding Information on a Menu: Linking Menu Organization to the User's Goals

Abstract: Design paradigms often ignore the diverse goals users bring to the computer interface. Any human-computer interaction can be viewed as a marriage of two systems: The user begins the interaction by formulating an information goal, and the computer software meets that goal with a sometimes complex list of potential topic areas. The user then accesses that topic list through the computer interface. Part of the act of accessing the topic list is selecting a potential topic, and this action is often supported by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…While uniform distribution does not reflect menu usage in real worlds [8,9,10,12], it has been used in many menu studies [2,4,5,16,20] because it is easy to experimentally control. In contrast, Zipfian distribution is more difficult to control in spite of better modelling item frequency distribution in common applications [6,8,9].…”
Section: The Uniform and Zipfian Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While uniform distribution does not reflect menu usage in real worlds [8,9,10,12], it has been used in many menu studies [2,4,5,16,20] because it is easy to experimentally control. In contrast, Zipfian distribution is more difficult to control in spite of better modelling item frequency distribution in common applications [6,8,9].…”
Section: The Uniform and Zipfian Distributionsmentioning
confidence: 99%
“…While it is well known [6,8,9], the consequences of the distribution for behavior have not been systematically investigated. Indeed, many previous studies rely either on a Uniform distribution [2,4,5,16,20] when comparing selection time, or a variant of a Zipfian distribution [1,11] when focusing on the average menu selection time. However, it is unclear if these observations hold when given a different, and more ecologically plausible, frequency distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, other categories could arise as indicated by some other participants, such as the division between important and less important metadata elements or based on their frequency of use for relevance judgment. These types of categorisation have been proposed by researchers in human computer interaction and menu design research who argued that items should be grouped either in terms of similarity, importance or frequency of use (Mehlenbacher, 1989;Shneiderman & Plaisant, 2004;Liu, et al, 2002).…”
Section: Structure Of Metadata Elementsmentioning
confidence: 99%
“…It is perhaps not surprising then that since the inception of HCI there has been a sustained interest in studying visual search [3,4,6,7,[9][10][11]13,15].…”
Section: Introductionmentioning
confidence: 99%
“…These tasks have been extensively studied in the literature, but separately -there have been surprisingly few attempts to compare how people perform these different kinds of search tasks. What few studies there have been have found that known-item searches are faster and more accurate than semantic searches [12,13]. However, these early studies did not make use of eye-tracking techniques to investigate underlying changes in search strategy.…”
Section: Introductionmentioning
confidence: 99%